Scope of Public Law Studies - Wiwithkhunakorn, Sirivadee (Interdisciplinary Academic and Research Journal, 2022)
Public law is a law that addresses the legal statutes concerning the status and powers of parents as well as the relationship between parents and their subordinates; (1) The legal group relating to the existence of states, namely International Law, Urban Litigation Division, and Constitutional Law, which these two branches of law have in common is that it is a law on sovereignty without any other higher power to enforce it, both branches of law are based on the intention of coexistence. (2) A group of laws related to the operation of the State, namely administrative law and fiscal law, is a law that governs the day-to-day operations of states and other legal entities under public law and is a law that governs citizens and taxpayers are regularly exposed.